The Influence of Linguistic Intelligence and Parent’s Role Toward English Achievement at Private Senior High School in Depok - muthia mubasyira (Scope : Journal of English Language Teaching, 2018)
The aim of this research is to know the influence of linguistic intelligence and parent’s role towards English achievement at private senior high school in Depok, West Java. The data for linguistic intelligence is taken from worksheet through test, meanwhile the data for parent’s role is taken from questionnaire. Then the data for English achievement is taken from the score of English in students’ academic record which is familiar called rapor. Based on the result of the data analysis, it is known that coefficient correlation (R) = 0,742 and determination coefficient is 55,1%. It means that there are significant and strong influence of linguistic intelligence and parent’s role towards English achievement. English is influenced by linguistic intelligence and parent’s role for 55,1%. Meanwhile, the rest 44,9% is influenced by other factors. Futhermore, the test of hypotheses through regression analysis make the result for regression equality Y = 44,93 + 1,050 X1 + 0,251 X2 . the result for regression equality significant test is got the score of Sig = 0,000 and Fobserved = 53,389 so Sig score < 0,05 And Fobserved > Ftable so Ho is rejected and H1 is accepted. It means that regression coefficient is significant. The conclusion is there are strong and significant influence of linguistic intelligence and parent’s role towards English achievement at private senior high school in Depok.Keywords: Linguistic Intelligence, Parent’s Role, English Achievement.